Performance evaluation and self-designated benchmark indexes in the mutual fund industry - Sensoy, Berk A. (Journal of Financial Economics, 2009)
Almost one-third of actively managed, diversified U.S. equity mutual funds specify a size and value/growth benchmark index in the fund prospectus that does not match the fund's actual style. Nevertheless, these “mismatched” benchmarks matter to fund investors. Performance relative to the specified benchmark is a significant determinant of a fund's subsequent cash inflows, even controlling for performance measures that better capture the fund's style. These incremental flows appear unlikely to be rational responses to abnormal returns. The evidence is consistent with the notion that mismatched self-designated benchmarks result from strategic fund behavior driven by the incentive to improve flows.